1996
DOI: 10.1071/ea9960861
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irrigation on leaf gas exchange and yield of cashew in northern Australia

Abstract: Gas exchange, leaf water status, soil water use and nut yield of cashew trees were monitored during the reproductive phase in 2 consecutive years (1988 and 1989). Treatment 1 comprised continuous irrigation from the end of the wet season in April until harvest in October; T2, irrigation between flowering (mid June) and harvest; and T3, no irrigation. Irrigation was applied by under-tree sprinkler at 43 mm/week in 1988 and 64 mm/week in 1989. Measurement of leaf gas exchange, chlorophyll content and nut product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 2 publications
2
10
0
2
Order By: Relevance
“…In fact, for dwarf cashew plants cultivated in drier conditions such as that of the semi-arid region of Piaui State, northeastern Brazil, with a low average precipitation, an elevated rate of evapotranspiration and a deep water table -conditions in which the plants would certainly suffer a water deficit -the average photosynthetic rate of the cashew plants was 10 µmol m -2 s -1 (unpublished results). Consistent with these data, Schaper et al (1996) in northern Australia also found significant differences in photosynthetic rates of irrigated and non-irrigated cashew trees, with higher differences during October, when the level of water in the soil was at its lowest and the plants were in full fruit. …”
Section: Effect Of Irrigation On Cashew Tree Photosynthesissupporting
confidence: 75%
“…In fact, for dwarf cashew plants cultivated in drier conditions such as that of the semi-arid region of Piaui State, northeastern Brazil, with a low average precipitation, an elevated rate of evapotranspiration and a deep water table -conditions in which the plants would certainly suffer a water deficit -the average photosynthetic rate of the cashew plants was 10 µmol m -2 s -1 (unpublished results). Consistent with these data, Schaper et al (1996) in northern Australia also found significant differences in photosynthetic rates of irrigated and non-irrigated cashew trees, with higher differences during October, when the level of water in the soil was at its lowest and the plants were in full fruit. …”
Section: Effect Of Irrigation On Cashew Tree Photosynthesissupporting
confidence: 75%
“…Observou-se, ainda, uma tendência de aumento do número de flores perfeitas abertas nas plantas irrigadas (2,41) quando comparadas às plantas não-irrigadas (2,16), o que sugere que o déficit hídrico provoca a redução do número de flores estaminadas e perfeitas produzidas. O padrão de florescimento observado neste estudo mostrou-se consistente com o obtido por Schaper et al (1996) na região Nordeste da Austrá-lia, em plantas de cajueiro irrigadas e não-irrigadas.…”
Section: Resultsunclassified
“…Relataram, ainda, que após a segunda semana o número de flores estaminadas aumentou acentuadamente, enquanto o de flores perfeitas diminuiu, e, por via de conseqüência, reduziu também a razão sexual durante o restante do perí-odo de florescimento. Schaper et al (1996), também na Austrália, estudando plantas de cajueiro irrigadas por aspersão sob-copa, não observaram efeitos da irrigação no número de flores perfeitas produzidas, as quais variaram de 0 a 15 por panícula.…”
Section: Resultsunclassified
“…Nonetheless, both CO 2 assimilation rates values are within the range described for adult cashew trees in other studies. Under natural conditions, Balasimha (1991) and Palanisamy & Yadukumar (1993) reported maximum CO 2 assimilation rates of about 10 µmol m -2 s -1 , while researches in Australia reported values up to 20 µmol m -2 s -1 (Schaper & Chacko, 1993;Schaper et al, 1996;Blaikie et al, 2001). …”
Section: Resultsmentioning
confidence: 99%
“…The lack of information about the species is due to limited research considering physiological aspects (Marler et al, 1994). Some studies were developed in Australia, such as: Schaper & Chacko (1993), on the influence of leaf age and branch girdling on gas exchange; Schaper et al (1996), on the effects of irrigation on gas exchange and leaf water status; and Blaikie & Chacko (1998) and Blaikie et al (2001), on sap flow and leaf photosynthesis as affected, respectively, by soil drying and irrigation strategies. Balasimha (1991), and Palanisamy & Yadukumar (1993) have also studied the photosynthetic characteristics of adult cashew trees in India.…”
Section: Introductionmentioning
confidence: 99%